Rancangan Proses Bisnis Berbasis Pengendalian Internal Untuk Meminimalisir Keterlambatan Pembayaran Hutang Vendor - Azira Azira; Alfonsa Dian Sumarna (Universitas Veteran Bangun Nusantara, 2023)
This research discusses the problems faced by PT. NP is about the absence of standard operating procedures for debt repayment, which is resulting in obstructed debt payments and often found inappropriate documents due to no checking by default. The purpose of this study is to contrive a debt payment procedure for debt repayment transactions and follow a good internal control framework. This research uses a qualitative descriptive method. Using primary and secondary data. A data collection technique uses observation and interviews. The conclusion of the study is that the problem of debt repayment can be minimized by designing a procedure. The procedure includes workflow process in narration and flowchart, related documentation, related division, and also implementation of internal control based on the COSO framework. Then the documents used in the debt payment SOP are complete and follow the rules of good and correct internal control.